Short-Term Passive Greenspace Exposures Have Little Effect on Nasal Microbiomes: A Cross-Over Exposure Study of a Māori Cohort - Brame, Joel E; Warbrick, Isaac; Heke, Deborah; Liddicoat, Craig; Breed, Martin F (Elsevier, 2024)
Indigenous health interventions have emerged in New Zealand aimed at increasing people's interactions with and exposure to macro and microbial diversity. Urban greenspaces provide opportunities for people to gain such exposures. However, the dynamics and pathways of microbial transfer from natural environments onto a person remain poorly understood. Here, we analysed bacterial 16S rRNA amplicons in air samples (n = 7) and pre- and post-exposure nasal samples (n = 238) from 35 participants who had 30-min exposures in an outdoor park. The participants were organised into two groups: over eight days each group had two outdoor park exposures and two indoor office exposures, with a cross-over study design and washout days between exposure days. We investigated the effects of participant group, location (outdoor park vs. indoor office), and exposures (pre vs. post) on the nasal bacterial community composition and three key suspected health-associated bacterial indicators (alpha diversity, generic diversity of Gammaproteobacteria, and read abundances of butyrate-producing bacteria). The participants had distinct nasal bacterial communities, but these communities did not display notable shifts in composition following exposures. The community composition and key health bacterial indicators were stable throughout the trial period, with no clear or consistent effects of group, location, or exposure. We conclude that 30-min exposure periods to urban greenspaces are unlikely to create notable changes in the nasal microbiome of visitors, which contrasts with previous research. Our results suggest that longer exposures or activities that involves closer interaction with microbial rich ecological components (e.g., soil) are required for greenspace exposures to result in noteworthy changes in the nasal microbiome.
Keywords: Aerobiome; Microbial ecology; Microbiome; Nasal microbiome; Urban greenspaces; Aerobiome; Microbial ecology; Microbiome; Nasal microbiome; Urban greenspaces; 3107 Microbiology; 31 Biological Sciences; Clinical Trials and Supportive Activities; Health Effects of Indoor Air Pollution; Clinical Research; Prevention; Social Determinants of Health; Microbiome; 2.2 Factors relating to the physical environment; 03 Chemical Sciences; 05 Environmental Sciences; 06 Biological Sciences; Toxicology; 31 Biological sciences; 34 Chemical sciences; 41 Environmental sciences; Adult; Female; Humans; Male; Middle Aged; Young Adult; Air Microbiology; Air Pollutants; Bacteria; Cohort Studies; Cross-Over Studies; Environmental Exposure; Maori People; Microbiota; New Zealand; Nose; Parks, Recreational; RNA, Ribosomal, 16S; Nose; Humans; Bacteria; RNA, Ribosomal, 16S; Air Pollutants; Cohort Studies; Cross-Over Studies; Air Microbiology; Environmental Exposure; Adult; Middle Aged; New Zealand; Female; Male; Young Adult; Microbiota; Parks, Recreational; Maori People; Adult; Female; Humans; Male; Middle Aged; Young Adult; Air Microbiology; Air Pollutants; Bacteria; Cohort Studies; Cross-Over Studies; Environmental Exposure; Maori People; Microbiota; New Zealand; Nose; Parks, Recreational; RNA, Ribosomal, 16S